2017
DOI: 10.4236/sar.2017.54004
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Diet on Saliva

Abstract: The aim of this scientific research was to study the influence of various diets (ketogenic, low carb, mixed) on teeth and saliva structure of healthy individuals. The health condition of teeth and the influence of diet (sweets, water intake) were investigated using the questionnaires which were statistically processed by descriptive and inductive statistics. Saliva was examined using synchronous fluorescent fingerprint (SFF) and atomic force microscopy (AFM). The statistical evaluation of answers of respondent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
2
3
0
1
Order By: Relevance
“…To the best of our knowledge, this is the rst paper to study the histological effect of a keto diet on the structure of salivary glands. Therefore, our result is nearly in agreement with Tomečková et al (2017) [25], who studied the effect of KD on human saliva compared to a low-carb diet and mixed them by atomic force microscopy. They found that the crystals in the KD group had a larger size, from 1000 nm to 2000 nm, and the highest surface roughness reached 84.9 nm, in comparison to the mixed diet, which showed crystal sizes from 400 nm to 1000 nm with an increased surface roughness of 25.2 nm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…To the best of our knowledge, this is the rst paper to study the histological effect of a keto diet on the structure of salivary glands. Therefore, our result is nearly in agreement with Tomečková et al (2017) [25], who studied the effect of KD on human saliva compared to a low-carb diet and mixed them by atomic force microscopy. They found that the crystals in the KD group had a larger size, from 1000 nm to 2000 nm, and the highest surface roughness reached 84.9 nm, in comparison to the mixed diet, which showed crystal sizes from 400 nm to 1000 nm with an increased surface roughness of 25.2 nm.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, the KD changes from epileptic therapy to a traditional diet used for weight loss. However, it may have some side effects on long-term use [25]. In the present study, the aim was to test the null hypothesis that there is no difference between the three groups against the alternative group.…”
Section: Discussionmentioning
confidence: 95%
“…Currently, the KD changes from epileptic therapy to a traditional diet used for weight loss. However, it may have some side effects on long-term use [ 26 ]. In the present study, the main objective was to test the null hypothesis that there is no difference between the three groups against the alternative group.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is further exacerbated by alimentary habits or lifestyles such as consuming sweet food and drinks. 18,19,20 Xerostomia were the most common oral manifestations found due to the usage effects of combination inhalation drug corticosteroid and β2-agonist. Therefore, methods to prevent and minimalize oral manifestation were needed.…”
Section: Discussionmentioning
confidence: 99%